Serological response after SARS-CoV2 vaccination in healthcare workers: a multicenter study - Visci, Giovanni; Zunarelli, Carlotta; Mansour, Ihab; Porru, Stefano; De Palma, Giuseppe; Duval, Xavier; Monaco, Maria Grazia Lourdes; Spiteri, Gianluca; Carta, Angela; Lippi, Giuseppe; Verlato, Giuseppe; Sansone, Emanuele; et al. (La Medicina del Lavoro, 2022)
Introduction: Characterizing immunological response following COVID-19 vaccination is an important public health issue. The objectives of the present analysis were to investigate the proportion, level and the determinants of humoral response from 21 days to three months after the first dose in vaccinated healthcare workers (HCWs). Methods: We abstracted data on level of anti-SARS-CoV-2 Spike antibodies (IgG) and sociodemographic characteristics of 17,257 HCWs from public hospitals and public health authorities from three centers in Northern Italy who underwent COVID-19 vaccination (average 70.6 days after first dose). We fitted center-specific multivariate regression models and combined them using random-effects meta-analyses. Results: A humoral response was elicited in 99.3% of vaccinated HCW. Female sex, young age, and previous COVID-19 infection were predictors of post-vaccination antibody level, and a positive association was also detected with pre-vaccination serology level and with time between pre- and post-vaccination testing, while a decline of antibody level was suggested with time since vaccination. Conclusions: These results stress the importance of analyzing retrospective data collected via occupational health surveillance of HCWs during the COVID-19 epidemic and following vaccination. They need to be confirmed in larger series based on prospectively collected data.